Connecting - Helen Walker; Louise Morgan; Danielle Sahm; Laurence Musgrove; Rae Ann DeRosse; Joonna Smitherman Trapp; Beverly Faxon (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Connecting - Helen Walker Louise Morgan - Email about the Ego Danielle Sahm - The Poet Rewritten Laurence Musgrove - People Get Ready Rae Ann De Rosse - Authority Issues Joonna Smitherman Trapp - The Importance of Being Ernie Beverly Faxon - Why I Read Them Poetry